Learning General World Models in a Handful of Reward-Free Deployments - Xu, Yingchen; Parker-Holder, Jack; Pacchiano, Aldo; Ball, Philip J.; Rybkin, Oleh; Roberts, Stephen J.; Rocktäschel, Tim (2022)
Abstract to come...